Prenatal Exposure to Nitrate in Drinking Water and Adverse Health Outcomes in the Offspring: a Review of Current Epidemiological Research - Pernille Jul Clemmensen; Jörg Schullehner; Nis Brix; Torben Sigsgaard; Leslie Thomas Stayner; Henrik Albert Kolstad; Cecilia Høst Ramlau-Hansen (Current Environmental Health Reports, 2023)
Purpose of Review Recently, several epidemiological studies have investigated whether prenatal exposure to nitrate from drinking water may be harmful to the fetus, even at nitrate levels below the current World Health Organization drinking water standard. The purpose of this review was to give an overview of the newest knowledge on potential health effects of prenatal exposure to nitrate. Recent Findings We included 13 epidemiological studies conducted since 2017. Nine studies investigated outcomes appearing around birth, and four studies investigated health outcomes appearing in childhood and young adulthood. Summary The reviewed studies showed some indications of higher risk of preterm delivery, lower birth weight, birth defects, and childhood cancer related to prenatal exposure to nitrate. However, the numbers of studies for each outcome were sparse, and some of the results were conflicting. We suggest that there is a need for additional studies and particularly for studies that include information on water consumption patterns, intake of nitrate from diet, and intake of nitrosatable drugs.